2009
DOI: 10.1007/s11192-009-0035-9
|View full text |Cite
|
Sign up to set email alerts
|

Why it has become more difficult to predict Nobel Prize winners: a bibliometric analysis of nominees and winners of the chemistry and physics prizes (1901–2007)

Abstract: We propose a comprehensive bibliometric study of the profile of Nobel Prize winners in chemistry and physics from 1901 to 2007, based on citation data available over the same period. The data allows us to observe the evolution of the profiles of winners in the years leading up to-and following-nominations and awarding of the Nobel Prize. The degree centrality and citation rankings in these fields confirm that the Prize is awarded at the peak of the winners' citation history, despite a brief Halo Effect observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 14 publications
0
50
0
1
Order By: Relevance
“…Gingras and Wallace found that academics who received a Nobel Prize saw a subsequent increase in citations to their articles [38]. Following this example, in order to evaluate whether presenting at TED leads to increased citations for academics, we compared the number of citations to an academic’s publications before and after the talk for the three years for which sufficient data were available.…”
Section: Resultsmentioning
confidence: 99%
“…Gingras and Wallace found that academics who received a Nobel Prize saw a subsequent increase in citations to their articles [38]. Following this example, in order to evaluate whether presenting at TED leads to increased citations for academics, we compared the number of citations to an academic’s publications before and after the talk for the three years for which sufficient data were available.…”
Section: Resultsmentioning
confidence: 99%
“…In this way it could be read as a general or technical description. There seems to be a belief among bibliometricians that citation counts, if appropriately normalized, can aid or replace peer judgments of quality for researchers (Bornmann & Daniel, 2006;Gingras & Wallace, 2010;Meho & Sonnenwald, 2000), journals (Garfield, 2005), and departments (Oppenheim, 1995(Oppenheim, , 1997Smith & Eysenck, 2002;van Raan, 2000), but that they do not directly measure quality because some high-quality work attracts few citations and some poor work attracts many.…”
Section: Organization Title Mentions As a Web Impact Measurementmentioning
confidence: 99%
“…A limitation of Google Pagerank is that it is not as suitable to calculating the author impact factor as the h-index. There are some papers in which authors proceed with analysis and discussion of Nobel prizes (see, for example, Ashton, 1978;Garfield, 1981Garfield, , 1986Garfield and Welljams-Dorof, 1992;Gingras and Wallace, 2010). However, only Ashton (1978) tried to propose a new method to predict Nobel prize winners.…”
Section: Technical Discussion Of Some Related Measuresmentioning
confidence: 99%
“…The comparison process helps to provide us with a deeper understanding of the issues related to this study and understand to the advantages and flaws of previous studies. There are also some other related works such as Ashton (1978), Garfield (1986), Garfield and Welljams-Dorof (1992) and Gingras and Wallace (2010). However, most of these works perform a citation analysis for Nobel Prize winners' publications rather than propose a method to predict them.…”
Section: Prog 482mentioning
confidence: 99%